The Unknown God - Dunn, Jacob P. (The biblical world, 1913)
A college student once said to a distinguished professor of history who had referred to the roads Solomon built: "Do you mean to tell us that Solomon was a real person? I thought he was just somebody in the Bible." That is the way too many persons feel about Paul. To make the apostle real he must be seen in connection with the very real world in which he lived. Mr. Dunn attempts to show in a rather novel fashion Paul's relation to Platonism. His reconstruction of the address of Paul at Athens is, of course, only conjecture, but does it not help us to understand the effect which it had upon thoughtful persons?